Synthesis, Characterization, and Visible Light Curing Capacity of Polycaprolactone Acrylate. (8th May 2018) - Tzeng, Jy-Jiunn; Hsiao, Yi-Ting; Wu, Yun-Ching; Chen, Hsuan; Lee, Shyh-Yuan; Lin, Yuan-Min
Abstract : Polycaprolactone (PCL) is drawing increasing attention in the field of medical 3D printing and tissue engineering because of its biodegradability. This study developed polycaprolactone prepolymers that can be cured using visible light. Three PCL acrylates were synthesized: polycaprolactone-530 diacrylate (PCL530DA), glycerol-3 caprolactone triacrylate (Glycerol-3CL-TA), and glycerol-6 caprolactone triacrylate (Glycerol-6CL-TA). PCL530DA has two acrylates, whereas Glycerol-3CL-TA and Glycerol-6CL-TA have three acrylates. The Fourier transform infrared and nuclear magnetic resonance spectra suggested successful synthesis of all PCL acrylates. All are liquid at room temperature and can be photopolymerized into a transparent solid after exposure to 470 nm blue LED light using 1% camphorquinone as photoinitiator and 2% dimethylaminoethyl methacrylate as coinitiator. The degree of conversion for all PCL acrylates can reach more than 80% after 1 min of curing. The compressive modulus of PCL530DA, Glycerol-3CL-TA, and Glycerol-6CL-TA is65.7 ± 12.7, 80.9 ± 6.1, and32.1 ± 4.1 MPa, respectively, and their compressive strength is5.3 ± 0.29, 8.3 ± 0.18, and3.0 ± 0.53 MPa, respectively. Thus, all PCL acrylates synthesized in this study can be photopolymerized and because of their solid structure and low viscosity, they are applicable to soft tissue engineering and medical 3D printing.